Casebook of indigenous business practices in Africa. volume 2 : trade, production and financial services - Adeola, Ogechi (Emerald Publishing Limited, 2023)
Africa's unique and diverse culture, embedded in age-long business practices, presents an interesting proposition for advancing indigenous knowledge and building sustainable structures. Casebook of Indigenous Business Practices in Africa is a collection of case studies across Northern, Eastern, Central, Western and Southern parts of Africa. Indigenous enterprises contribute to the economic prosperity of Africa and are an essential part of the continent's business ecosystem. Contributing authors to this two-volume edited work explore the inherent potential of indigenous practices in bolstering business performance and stimulating social and economic development. The first volume focuses on Apprenticeship, Craft, and Healthcare, while this second volume considers Trade, Production and Financial Services, in featured African countries. Indigenous business practices hold great prospects for economic advancement in Africa, despite the dominance of Western business methods, which, although beneficial, are yet to drive the continent's developmental agenda. By identifying and exploring the unique features of these practices, multiple actors, including entrepreneurs, policymakers, students, educators, and practitioners, are provided with context-based information that can foster social and economic empowerment across the continent. The book extends the frontier of knowledge on the role of cultural orientation, values, and traditions in achieving a more prosperous Africa through the development of indigenous business knowledge.